Knowledge of Students as Orthodontic Users in Maintaining Dental and Oral Hygiene - Siti Alfiyah Rusdi; Emilda Sari (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
Interest and awareness to take care of dental and oral hygiene is upstanding. Orthodontics besides filling and extraction in the practice of dental and oral health is in use. Maintaining oral hygiene during orthodontic treatment will greatly result in good gingival health, which can be seen in the final results of orthodontic treatment.This paper outlines the knowledge of maintaining oral and dental hygiene by orthodontic users among students in Poltekkes Kemenkes Banjarmasin. This study is descriptive research. The research was conducted with a cross-sectional approach. The research took place at Poltekkes Kemenkes Banjarmasin. Sixty students became the population. The research sample was selected by Total Sampling, namely all orthodontic users, totaling 50 students.Remarkably, the knowledge of maintaining oral and dental hygiene of orthodontic users are good, that is 5 students with a percentage of 10%, fair category as many as 32 students with a percentage of 64%, and a bad category as many as 13 students or 26%.In conclusion, the knowledge of most students of Poltekkes Kemenkes Banjarmasin as the users of orthodontics is fair in maintaining dental and oral hygiene. It is expected that students will pay more attention and expand their knowledge about how to keep their teeth and mouth clean while using orthodontics in order to obtain maximum orthodontic treatment results.